Right aortic arch with an aberrant left subclavian artery and aortic coarctation including a descending aortic aneurysm - Frantisek Sabol (Journal of Cardiothoracic Surgery, 2019)
Abstract Backround The right aortic arch and aortic coarctation are rare congenital anomalies with the incidence of 0.1% and 0.03–0.04%. We present a case report of a 51-year-old woman with the right aortic arch with aberrant left subclavian artery and coarctation of the aorta with post-stenotic aneurysm. Case presentation Resection of the coarctation and aneurysm with replacement by tubular prosthesis was performed on partial cardiopulmonary bypass via femoral vessels. Conclusion Partial cardiopulmonary bypass is an applicable method for ensuring the perfusion of the distal part of the body and an aberrant left subclavian artery is not a contraindication of this technique.